Legal regulation of the system of public administration entities providing the administrative and legal regime of special economic zones - O. A. Lakaev (Правоприменение, 2022)
The subject of the article is scientific ideas that determine the essence and content of the system of public administration entities that ensure the administrative and legal regime of special economic zones. The author analyzes constitutional norms and provisions of legislative and subordinate acts that form the legal basis for their organization and functioning, the practice of their application.The purpose of the article is to scientifically substantiate the improvement of the system of subjects for ensuring the administrative and legal regime of special economic zones in order to increase the level of their interaction and the progressive economic development of the respective territories.The methodology. The author uses general scientific methods were used (formal-logical, systemic-structural and dialectical methods), as well as private scientific methods, such as the formal-legal, comparative-legal method, the method of interpretation of legal norms.The main results, scope of application. The article reveals the current state of the legal regulation of the system of subjects of public administration of special economic zones in terms of correlation with the new constitutional norms on public authority, characterizes public administration in special economic zones from the point of view of the systemic unity of its constituent elements. The article reveals the shortcomings of this system from the standpoint of completeness, the state of interrelations between its various elements, which cause a decrease in the investment attractiveness of special economic zones, which do not contribute to the creation of new industries and the production of competitive products.The paper substantiates the need to develop a balanced model of organization and functioning of the corresponding legal regime developed with the participation of business representatives. The article proposes a more complete version of the system of subjects of public administration in comparison with the statutory one, including not only those that form a single centralized management system, but also others - the executive and administrative bodies of municipalities, as well as collective formations that are not included in the system of state bodies. and municipal authorities (supervisory boards, expert councils). Based on the identified shortcomings in the organization of expert councils of special economic zones, the article formulates scientifically based proposals for improving the current legislation.Conclusions. It is necessary to bring the Federal Law “On Special Economic Zones in the Russian Federation” into line with the new provisions of the Russian Constitution on public authority. It will let legalize the existing system of public administration of special economic zones,. Rules on the special economic zones administration should be set out in a chapter entitled “Peculiarities of Implementation public authorities in special economic zones”. The idea was formulated to describe in the proposed chapter a list of all subjects of public administration of special economic zones - the Russian Government, the authorized federal executive body, authorized executive bodies of the constituent entities of the Russian Federation, executive and administrative bodies of municipalities, management companies, supervisory boards and expert councils and determine the powers of each of them.